DEVELOPMENTALISME EKONOMI DI PULAU GILI TRAWANGAN KECAMATAN PEMENANG KABUPATEN LOMBOK UTARA PROVINSI NUSA TENGGARA BARAT: Studi Komparatif Konsep Pembangunan Antara Sistem Ekonomi Islam Dan Sistem Ekonomi Kapitalis - Al-Muhajir, Achmad; Supriyanto (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2022)
Economics and needs encourage people to continue to develop in solving problems about the economy and to meet the needs in their lives. Economic problems and fulfillment of needs are not only individual or personally borne, but also collective or shared responsibility. Thought about what system is considered appropriate for a country without stopping done. A good economic system cannot be determined by its ideology, because every economic system experiences resistance from other system. In addition to the Capitalist and Socialist values which have filled the world economy, Islam also contributes to economic thinking, even before Adam Smith with his capitalism